Integrating visuo-haptic simulators for active learning to explore the concept of Boyle's Law - Montes-Isunza, Sebastián; Lozada-Flores, Octavio; Berumen-Glinz, Lorena Alexandra; Escobar-Castillejos, Daisy; Escobar-Castillejos, David (Frontiers in Education, 2026)
IntroductionTraditional approaches to teaching physics often struggle to engage students and to convey abstract concepts such as gas laws in a meaningful way. This challenge is particularly evident for learners accustomed to interactive and technology-mediated environments. Recent advances in embodied cognition and active learning suggest that multi-sensory interaction may enhance engagement and conceptual understanding. Visuo-haptic simulators represent a promising approach by combining visual and tactile feedback to support experiential learning.MethodsThis study developed a visuo-haptic simulator designed to support the exploration of Boyle's Law through interactive manipulation of pressure and volume variables. The simulator provided real-time visual feedback and proportional haptic resistance to represent changes in gas behavior. Thirty-nine undergraduate engineering students interacted with the simulator in controlled laboratory sessions. A mixed-methods approach was used to evaluate students' perceptions, combining the End-User Computing Satisfaction (EUCS) survey with semi-structured interviews.ResultsSurvey results indicated high levels of satisfaction in the dimensions of accuracy, ease of use, and timeliness, reflecting students' confidence in the simulator's responsiveness and reliability. Qualitative findings revealed strong engagement and motivation, with participants reporting that tactile feedback helped them intuitively understand the inverse relationship between pressure and volume. Some usability challenges related to interface layout were also identified.DiscussionThe findings suggest that visuo-haptic simulators can promote active engagement and support embodied understanding of abstract physics concepts by linking theoretical relationships to sensory experience. Students perceived the simulator as a valuable complement to traditional instruction and expressed interest in its application to other scientific topics. While learning outcomes were not directly measured, the results highlight the potential of visuo-haptic tools to enhance motivation and experiential learning in physics education. Future work will focus on assessing learning gains in classroom settings and extending the approach to additional thermodynamics concepts.